After the Pink Tide Corporate State Formation and New Egalitarianisms in Latin America - Gold, Marina (Egalitarianism, 2020)
The left-wing Pink Tide movement that swept across Latin America seems now to be overturned, as a new wave of free-market thinkers emerge across the continent. This book analyses the emergence of corporate power within Latin America and the response of egalitarian movements across the continent trying to break open the constraints of the state. Through an ethnographically grounded and localized anthropological perspective, this book argues that at a time when the regular structures of political participation have been ruptured, the Latin American context reveals multiple expressions of egalitarian movements that strive (and sometimes momentarily manage) to break through the state's apparatus.